Numerical Study on the Effect of Concrete Grade on the CFT Circular Column’s Behavior under Axial Load - Badarloo, Baitollah; Jafari, Faezeh (Civil Engineering Journal, 2019)
Concrete-filled tubular (CFT) column improves the structure properties under different load pattern, so that it should be designed under two main load patterns (static and cyclic load) using current design method such as Finite Element Method (FEM) and analytical method (guideline equation). In this research, a CFT column with specific dimensions is modeled by using ABAQUS finite element software; the target of this study is to conduct a pushover analysis and also a hysteresis analysis under cyclic loading. Then, the concrete grade and percentage of column reinforcement were altered using the FEM, and eventually, compared with the results of analytical equations to measure the safety level of analytical equations. For this purpose, the CFT columns with C20, 30, 40 & 50 concrete cores were modeled with and without reinforcement, and the effect of concrete grade on the capacity of column was studied. In addition, MATLAB software was used to obtain beta index and load capacity design for the CFT column. The results demonstrated that the columns designed in accordance with the AISC have a good performance under the cyclic and static loading. The safety level of design equations ranged between 3 and 5, and the columns could resist higher loads (about 2.5-3.5 times) through the design by ABAQUS.